2012
DOI: 10.5194/nhess-12-2811-2012
|View full text |Cite
|
Sign up to set email alerts
|

The CASA quantitative precipitation estimation system: a five year validation study

Abstract: Abstract.Flooding is one of the most common natural hazards that produce substantial loss of life and property. The QPE products that are derived at high spatiotemporal resolution, which is enabled by the deployment of a dense radar network, have the potential to improve the prediction of flash-flooding threats when coupled with hydrological models. The US National Science Foundation Engineering Research Center for Collaborative Adaptive Sensing of the Atmosphere (CASA) is dedicated to revolutionizing our abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…A key drawback of X-band radar wavelength in rainfall estimation is the severe rain-path attenuation, but dual-polarization radar technology can now mitigate this effect through the development of robust attenuation correction schemes [31][32][33][34][35][36][37][38][39][40][41]. As a result, progress in the X-band dual-polarization rainfall estimation has enhanced the applicability of such radar (typically mobile) systems for flood modeling applications in urban areas [42][43][44][45] and in complex terrain basins [22][23][24][25]31,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…A key drawback of X-band radar wavelength in rainfall estimation is the severe rain-path attenuation, but dual-polarization radar technology can now mitigate this effect through the development of robust attenuation correction schemes [31][32][33][34][35][36][37][38][39][40][41]. As a result, progress in the X-band dual-polarization rainfall estimation has enhanced the applicability of such radar (typically mobile) systems for flood modeling applications in urban areas [42][43][44][45] and in complex terrain basins [22][23][24][25]31,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Atmosphere 2017, 8,25 4 of 20 interconnected with a Digital Terrain Model (DTM). This procedure has been implemented according to the 3D spatial data infrastructure described in Section 3.1.…”
Section: Set Up Of the Radar Systemsmentioning
confidence: 99%
“…The choice of such a scan configuration that includes ten elevations with the maximum range was made to meet two requirements: the necessity of monitoring the full area and of finding the optimal set Atmosphere 2017, 8,25 5 of 20 of elevations to be used for the clutter signal filtering. The scan repetition time has been set to 15 min, according to the time needed for processing ten elevations.…”
Section: Real Time Operativitymentioning
confidence: 99%
“…In this respect, some previous works have highlighted a correlation between dual polarization radar variables and microphysical processes of stroke initialization [12][13][14][15][16][17][18]. However, most of the local weather services cannot afford dual polarization technology, and, on top of this, the increasing diffusion of small networks of single polarization X band radars for urban and small catchment monitoring is a demonstration of a constant interest toward these systems and the related applications [19].The measurements that are provided by single polarization weather radars, although with some well-known limitations, can still provide some exploitable information for the hydrometeor detection in the mixed-phase region of a thunderstorm. In this respect, several studies [20][21][22][23][24] have found links between the presence of graupel at different environmental levels and the occurrence of a strong reflectivity core.…”
mentioning
confidence: 99%
“…In this respect, some previous works have highlighted a correlation between dual polarization radar variables and microphysical processes of stroke initialization [12][13][14][15][16][17][18]. However, most of the local weather services cannot afford dual polarization technology, and, on top of this, the increasing diffusion of small networks of single polarization X band radars for urban and small catchment monitoring is a demonstration of a constant interest toward these systems and the related applications [19].…”
mentioning
confidence: 99%